Association analyses of novel polymorphisms in the MMP-1 promoter gene with osteoarthritis secondary to hip dysplasia in dogs - Fassa, V.B. (2010)
Hip dysplasia (HD) is a polygenic disease characterized by joint laxity and lack of congruence leading to osteoarthritis (OA). Under many pathogenic conditions including arthritis, MMP-1 synthesis is augmented. The MMP-1 gene promoter contains cytokine response elements, transcription factors AP-1 and SAF-1 that are increased in OA. The objective of the present study was to identify and characterize new polymorphisms of the canine MMP-1 promoter gene and evaluate their association with OA secondary to HD in different dog breeds. Based on the NCBI_006587 reference sequence, two novel polymorphisms, Indel CTGCCCT (bp31986794) and C>T (bpSNP 31986815) substitution were selected due their position in a consensus sequence belonging to a SAF-1 response element. Data was uploaded in the GenBank database (accession number GQ475524 and GQ475525). 125 dogs of different breeds were sampled and hip status was evaluated through ventrodorsal extended-hip radiographs. A chi-squared analysis was performed to test the association of the variables: breed, sex and genotype for each polymorphism with OA status (healthy and affected). No significant association (p>0.05) was found between any variable and OA secondary to HD. This study does not exclude MMP-1 as a gene responsible of OA secondary to HD in the breeds sampled because only the promoter sequence was evaluated.\n